Technical tips for endoscopic ultrasound-guided pancreatic duct access and drainage - Yousuke Nakai (Society of Gastrointestinal Intervention, 2020)
Endoscopic ultrasound (EUS)-guided pancreatic duct access and drainage can be achieved by EUS-guided rendezvous (EUS-RV) or EUS-guided pancreatic duct drainage (EUS-PD) by transmural stent placement. Although the procedure is utilized for further complex treatment such as intraductal lithotripsy in obstructive pancreatic duct stones, the procedure is technically difficult compared to other EUS-guided interventions. Recently, some devices are developed for EUS-guided pancreatic duct intervention. In this review, technical tips are reviewed in a step-by-step fashion from puncture, guidewire insertion, tract dilation to drainage. Given the advantage of EUS-guided approach, treatment algorithm of endotherapy for pancreatic indications should be further established especially in cases with surgically altered anatomy.